Minimal effect of bortezomib in reducing anti‐pig antibodies in human leukocyte antigen‐sensitized patients: a pilot study. (3rd September 2013) - Hara, Hidetaka; Bentall, Andrew; Long, Cassandra; Fang, Jason; Andreyev, Oleg; Lunz, John; Ezzelarab, Mohamed; Abu‐Elmagd, Kareem M.; Shapiro, Ron; Ayares, David; Stegall, Mark; Cooper, David K. C.
Abstract Background Bortezomib, a proteasome inhibitor used to treat multiple myeloma, has been administered (± plasma exchange ± intravenous immunoglobulin [IVIg]) in attempts to reduce antibodies against human leukocyte antigens (HLA) in sensitized patients undergoing organ transplantation. To our knowledge, bortezomib has not been investigated for its effect on natural anti‐pig antibodies. If bortezomib could reduce the production of anti‐pig antibodies, this would likely be beneficial to the outcome of pig organ grafts in primates. Methods Nine patients received bortezomib either to reduce anti‐HLA antibody levels before organ allotransplantation or to treat antibody‐mediated rejection. Patients at the Mayo Clinic (Group 1; n = 4) received bortezomib alone, whereas at the UPMC (Group 2; n = 5), this was combined with plasmaphereses ± IVIg in some cases. Anti‐pig IgM and IgG levels against wild‐type (WT) and α1, 3‐galactosyltransferase gene knockout (GTKO) pig aortic endothelial cells (flow cytometry—relative mean fluorescence intensity) and anti‐Gal IgM and IgG (ELISA–OD480 nm) were measured pre‐ and post‐bortezomib therapy. Results Mean anti‐pig IgM levels were 11.2 (WT) and 1.9 (GTKO) pre‐bortezomib treatment and 9.4 (WT: P = 0.02) and 1.7 (GTKO: P = 0.33) post‐bortezomib treatment, respectively. Mean anti‐pig IgG levels were 4.3 (WT) and 1.5 (GTKO) pre‐bortezomib treatment and 3.6 (WT: P = 0.21) and 1.4 (GTKO: P = 0.20) post‐bortezomib treatment, respectively. Mean anti‐Gal IgM and IgG levels were 0.7 and 1.1, respectively, pre‐treatment, and 0.6 (P = 0.03) and 1.1 (NS), respectively, post‐treatment. When the data were analyzed in Groups 1 and 2 separately, there were no significant differences between the pre‐ and post‐bortezomib levels of anti‐pig, anti‐non‐Gal, or anti‐Gal IgM or IgG. Conclusions From this limited study, we conclude that bortezomib might reduce anti‐Gal IgM levels in primates, but, in this respect alone, is unlikely to have any significant effect on the outcome of GTKO pig organ transplantation.